Modelling of a 3-phase Induction Motor under Open-phase Fault Using Matlab/Simulink - Mohammad Jannati; Tole Sutikno (Institute of Advanced Engineering and Science, 2016)
The d-q model of Induction Motors (IMs) has been effectively used as an efficient method to analyze the performance of the induction machines. This study presents a step by step Matlab/Simulink implementation of a star-connected 3-phase IM under open-phase fault (faulty 3-phase IM) using d-q model. The presented technique in this paper can be simply implemented in one block and can be made available for control purposes. The simulated results provide to show the behavior of the star-connected 3-phase IM under open-phase fault condition.